Motivasi Belajar Meningkatkan Motivasi Belajar Menggunakan Student Teams Achievement Divisions Pembelajaran IPA Kelas IV SDN 48 Ternate - Iwan Abdy; Andi Rahmadani; Dwi Widyastuti Nurharyanto (Kilau Publishing, 2025)
The research aims to determine the improvement of student learning motivation at SDN 48 Ternate in science subjects through the application of the Student Teams Achievement Divisions (STAD) model. The research design is classroom action research with the subjects being 22 students from the fourth grade of SDN 48 Ternate for the 2024/2025 academic year. This research was conducted in two cycles. Observation and Testing are the two main approaches to data collection. Student learning motivation consists of: the frequency of questions asked by students, student attention, student cooperation in groups, and the increase in learning resources utilized by students. In the pre-cycle, the average was 28.41%, in Cycle I the average was 44.32%, while in Cycle II the average reached 75%. From these results, it can be concluded that student motivation increased by 15.91% in Cycle I. The increase in student learning motivation in cycle II is greater than in cycle I by 30.68%, this indicates that the indicator of increased student learning motivation has been achieved. It can be concluded that the STAD method of learning has a positive effect and can enhance student learning motivation in science education.